Mediation Empowerment in Resolution of Civil Claims in State Court - Hariadi Hariadi (LEGAL BRIEF, 2023)
Mediation is a way of resolving disputes through a negotiation process to obtain an agreement between the parties assisted by a mediator as a facilitator, the provisions of which are regulated in Supreme Court Regulation Number 1 of 2016 concerning Mediation Procedures in District Courts. Mediation in court is the institutionalization and empowerment of peace (court-connected mediation) with the philosophical basis of Pancasila which is the basis of the Indonesian State, especially the fourth precept "Populist led by Wisdom of Wisdom in Deliberation/Representation". The fourth precept of the Pancasila, among other things, requires that efforts to resolve disputes, conflicts or cases be carried out through deliberations to reach a consensus that is filled with a spirit of kinship. Mediation in court is the result of the development and empowerment of peace institutions as stipulated in the provisions of Article 130 Herziene Inlandsch Reglemen (HIR) / 154 Rechtsreglemen voor de Buitengewesten (RBg) which requires a judge who hears a case to earnestly seek peace between the litigants. Efforts to resolve through Mediation apart from benefiting the parties are also beneficial for the Court because Mediation is expected to overcome the problem of accumulation of cases. however, the results of research at the Sengkang District Court Class IB and the Maros District Court Class IB show that the implementation of mediation is in accordance with Perma No. 1 of 2016 concerning Mediation Procedures at the District Court. However, there are several obstacles encountered in resolving civil lawsuit disputes in the District Court, namely egotism, external factors, educational factors, absence of the parties, passing the time limit, aspects of advocates and aspects of mediator judges.